2016
DOI: 10.1016/j.envint.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ATP-binding cassette transporters associated with maternal methylmercury disposition and infant neurodevelopment in mother-infant pairs in the Seychelles Child Development Study

Abstract: Background ATP-binding cassette (ABC) transporters have been associated with methylmercury (MeHg) toxicity in experimental animal models. Aims To evaluate the association of single nucleotide polymorphisms (SNPs) in maternal ABC transporter genes with 1) maternal hair MeHg concentrations during pregnancy and 2) child neurodevelopmental outcomes. Materials and methods Nutrition Cohort 2 (NC2) is an observational mother-child cohort recruited in the Republic of Seychelles from 2008–2011. Total mercury (Hg) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Epigenetic regulation is an important mechanism for modifying gene expression (Wang et al, ). As an important part of epigenetics, miRNAs play a vital role in regulation of transporter gene expression through binding the 3′‐UTR of genes (Koturbash et al, ; Wan et al, ; Engstrom et al, ; Kap et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic regulation is an important mechanism for modifying gene expression (Wang et al, ). As an important part of epigenetics, miRNAs play a vital role in regulation of transporter gene expression through binding the 3′‐UTR of genes (Koturbash et al, ; Wan et al, ; Engstrom et al, ; Kap et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these active transporters may also influence both inorganic and organic Hg uptake, distribution, and elimination at molecular level, modulating the cellular Hg efflux [ 5 , 41 , 42 ].…”
Section: Gene Classes Of Interest and Related Polymorphismsmentioning
confidence: 99%
“…Finally, attention must be drawn on the very recent study by Engström et al [ 41 ], based on a mother-child cohort from the Seychelles, a typically population suggestive of high fish intake and hair Hg concentrations. The authors identified in additional ABCC1 SNPs (rs215088, rs11075290, rs212093), ABCC2 (rs717620), and ABCB1 (rs2032582, rs1202169, rs10276499) some probable susceptibility markers to modulate the MeHg transport, distribution and elimination, based on the strong association of their genotypes with maternal hair Hg concentrations.…”
Section: Gene Classes Of Interest and Related Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate genes in the glutathione (GSH) metabolism pathway have been primarily considered since the formation of MeHg-GSH conjugates are thought to be key to excretion (Ballatori and Clarkson, 1983; Barcelos et al, 2013; Custodio et al, 2004; Engström et al, 2008; Engström et al, 2016; Gundacker et al, 2007). However, results have been inconsistent regarding the modifying role of these genes.…”
Section: Introductionmentioning
confidence: 99%